Comparison Between High‐Speed Video Observation of Sprites and Broadband Sferic Measurements. Issue 10 (11th May 2021) - Ren, Huan; Lu, Gaopeng; Cummer, Steven A.; Peng, Kang‐Ming; Lyons, Walter A.; Liu, Feifan; Li, Xiao; Wang, Yongping; Zhang, Shoubao; Cheng, Zhengwei
Abstract: High‐speed video observations of two sprites with halo features were analyzed with concurrent measurements of broadband magnetic sferics. Both events were produced by positive cloud‐to‐ground (CG) strokes. Moreover, the halo features appeared less than 0.5 ms after the return stroke, and the first sprite elements followed within 1  and 3 ms, respectively, for the two cases. The persistent charge transfer in the causative stroke from long continuing current can maintain the continuous glowing of existing sprite elements, and also may aid the vertical development and enhanced luminescence of later sprite elements. The observations with electric field ( E ‐field) simulations by the transmission line model provide evidence that the induction component of the lightning‐induced E ‐field contributes significantly to halo formation. Our results suggest additional measurements and analysis are needed to identify the specific role of induction E ‐field in addition to the well‐known quasi‐electrostatic (QE) field in the lightning‐induced impact on the mesosphere. Plain Language Summary: We analyze two cases of sprite observations demonstrating the halo feature that were both produced by positive cloud‐to‐ground (CG) strokes over a mesoscale convective system in the central United States. The first event was the brightest sprites observed on that night, while the second event was a dancing sprite event containing three sprite elements all following a single +CG. The broadband (<1 Hz–400 kHz) lightning sferic signals recorded at various ranges are analyzed in comparison with the high‐speed and low‐light‐level video to reveal the detailed development and evolution of sprite events. The first case contains an elves, halo, and sprite elements; the second case includes a halo as well as three sprite elements. In both case, the halo features appeared less than 0.5 ms after the return stroke. From this observation with relatively high time resolution and the simulation of lightning‐induced electrical field ( E ‐field) change at the height of halo formation, we attribute the occurrence of halo to the induction E ‐field from the initial portion (within 1 ms) of charge transfer in the causative stroke mainly. The continuous illumination of the existing sprite element and the time delay and vertical structure of following sprites are associated with the subsequent continuing current of causative strokes. Key Points: Two sprite events featured with halo were captured on the high‐speed video camera with coordinated broadband sferic data In both cases, the halo initiated within 0.5 ms after the causative return stroke The induction component of lightning‐induced transient E ‐field appears to make a considerable contribution to the halo formation